2013
DOI: 10.3109/00365548.2013.857044
|View full text |Cite
|
Sign up to set email alerts
|

Predominant association of Raoultella bacteremia with diseases of the biliary tract

Abstract: A case series of 14 patients with Raoultella bacteremia was compared with 28 Klebsiella oxytoca and 28 Klebsiella pneumoniae bacteremia cases. Forty-three percent of Raoultella bacteremia cases were associated with biliary tract disease, compared to 32% and 22% of patients with K. oxytoca and K. pneumoniae bacteremia, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…As well as the well-known clinical presentations of R. ornithinolytica infections, such as primary or cholangitis bloodstream infection, [3][4][5]7,14,16,18,20,22 catheter-related bloodstream infection, 8,26 biliary tract infection, 3-5 urinary tract infection, 5,15,21 and skin infection, 19,20 cases of respiratory infection including community-and hospital-acquired pneumonia and pleural effusion were also identified in this study, and these have been poorly reported. Boattini et al recently reported three cases of community-acquired pneumonia and three cases of hospital-acquired pneumonia among 25 cases of R. ornithinolytica infection over a 5-year period in six university hospital centres in Lisbon.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…As well as the well-known clinical presentations of R. ornithinolytica infections, such as primary or cholangitis bloodstream infection, [3][4][5]7,14,16,18,20,22 catheter-related bloodstream infection, 8,26 biliary tract infection, 3-5 urinary tract infection, 5,15,21 and skin infection, 19,20 cases of respiratory infection including community-and hospital-acquired pneumonia and pleural effusion were also identified in this study, and these have been poorly reported. Boattini et al recently reported three cases of community-acquired pneumonia and three cases of hospital-acquired pneumonia among 25 cases of R. ornithinolytica infection over a 5-year period in six university hospital centres in Lisbon.…”
Section: Discussionmentioning
confidence: 88%
“…This series of human infections caused by R. ornithinolytica managed at four university hospital centres in France over the last 12 years is the largest reported to date. A literature search identified 86 reported cases of R. ornithinolytica (formerly Klebsiella ornithinolytica), [3][4][5][6][7][8][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and half of these cases were reported in 2015. 10,12,[24][25][26] A high rate of hospital-acquired infection was observed in the present study (49%), which may be explained by the high proportion of patients who had undergone invasive procedures (48%) involving, for example, urinary catheters, mechanical ventilation, and port catheters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the incidence of isolation of R. ornithinolytica and R. planticola as human clinical pathogens is growing, mostly attributed to the use of molecular identification techniques in clinical microbiology laboratories that more precisely distinguish this genus and its species than those methods based on phenotypic features [2,3]. Until the middle of the 2015, 80 cases of bacteraemia due to Raoultella had been reported [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Most of the cases involved R. ornithinolytica and R. planticola and the primary sites of infection were diverse.…”
Section: Introductionmentioning
confidence: 99%